(untitled) (The Peerian Journal, 2023)
In this article, the development of industry, the increase in the population in the field of ecology has led to the emergence of new problems, the solution of this problem is becoming the main topic of regional and international conferences, as well as the problem of the lack of clean water, its neutralization and effective use, as well as water Issues such as the prevention of related risks, the initiative of the Republic of Uzbekistan in solving these problems, and the fact that providing clean water to the inhabitants of our planet is becoming one of the issues in the attention of the world community, have been philosophically, scientifically and theoretically analyzed.